2019
DOI: 10.1055/s-0039-1694081
|View full text |Cite
|
Sign up to set email alerts
|

Nanoceria and Its Biomedical Relevance

Abstract: Nanoceria is a nanosized particle preparation of cerium oxide. It shows mixture of cerium in the 3+ and 4+ states on the nanoparticle surface, giving it interesting redox properties. Nanoceria shows effective biological antioxidant properties, which makes it a great candidate for biomedical applications. Many studies have shown promising results on therapeutic potential of nanoceria in diseases like cancer, diabetes, atherosclerosis, and neurodegenerative diseases. Meanwhile, other studies explored biodistribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…This means they can be expressed as needed and automatically degenerate when necessary. However, cerium is not present in the human body, and the mechanism of its movement remains unclear . It is implied that cerium can be successfully ingested by cells in both normal and diseased states via multiple pathways.…”
Section: Future and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…This means they can be expressed as needed and automatically degenerate when necessary. However, cerium is not present in the human body, and the mechanism of its movement remains unclear . It is implied that cerium can be successfully ingested by cells in both normal and diseased states via multiple pathways.…”
Section: Future and Perspectivesmentioning
confidence: 99%
“…However, cerium is not present in the human body, and the mechanism of its movement remains unclear. 204 It is implied that cerium can be successfully ingested by cells in both normal and diseased states via multiple pathways. According to recent studies, CeO 2 NMs showed positive effects (such as scavenging ROS) and are considered promising biomedical materials in the majority of in vitro and in vivo analyses.…”
Section: Challenges In Exploration Of Mechanistic Insightmentioning
confidence: 99%
“…Some studies demonstrated toxic effects mainly in the form of oxidative stress and inflammation, whereas others indicated either protective, little or no effect 35,36 . Several studies reported that the uptake of CeO 2 NPs could induce oxidative stress and DNA damage, cell apoptosis, aberrant cell signalling, dephosphorylation of several substrates and alterations on the transcriptional and posttranslational levels 37 …”
Section: Introductionmentioning
confidence: 99%
“…35,36 Several studies reported that the uptake of CeO 2 NPs could induce oxidative stress and DNA damage, cell apoptosis, aberrant cell signalling, dephosphorylation of several substrates and alterations on the transcriptional and posttranslational levels. 37 In general, the cytotoxicity of NPs depends on many factors such as the particle size, shape, dose, synthesis method and surface charge. However, when it comes to CeO 2 NPs, the main driver for toxicity was found to be the percentage of surface content of Ce 3+ sites.…”
mentioning
confidence: 99%
“…Cerium oxide is used to assist with the healing of various tissues such as the bones, skin, cardiac, and nerves. Recently, the transfer of drugs and genes by CeO 2 nanoparticles and the use of CeO 2 as treatments for cancer and other diseases has received much attention [7,8].…”
Section: Introductionmentioning
confidence: 99%